Rapid transgenerational effects in Knautia arvensis in response to plant community diversity. (27th February 2017) - Rottstock, Tanja; Kummer, Volker; Fischer, Markus; Joshi, Jasmin
Summary: Plant species persistence in natural communities requires coping with biotic and abiotic challenges. These challenges also depend on plant community composition and diversity. Over time, biodiversity effects have been shown to be strengthened via increasing species complementarity in mixtures. Little is known, however, whether differences in community diversity and composition induce rapid transgenerational phenotypic adaptive differentiation during community assembly. We expect altered plant–plant and other biotic interactions (mutualists or antagonists) in high vs. low diverse communities to affect immediate within‐ and between‐species trait differentiations due to competition for light and nutrients. Three years after the initiation of a large‐scale, long‐term biodiversity experiment in Jena, Germany, we tested for effects of varying experimental plant community diversity (1–60 plant species; one to four plant functional groups) and composition (with or without legumes and/or grasses) on phenotypic differentiation and variation of the tall herb Knautia arvensis . We measured reproduction at different diversity levels in the Jena Experiment (residents hereafter) and, in an additional common garden experiment without competition, recorded subsequent offspring performance (i.e. growth, reproductive success and susceptibility to powdery mildew) to test for differentiation in phenotypic expression and variability. We observed phenotypic differences among diversity levels with reduced fecundity of K. arvensis residents in more diverse communities. In the next generation grown under common garden conditions, offspring from high‐diversity plots showed reduced growth (i.e. height) and lower reproduction (i.e. fewer infructescences), but increased phenotypic trait variability (e.g. in leaf width and powdery mildew presence) and also tended to be less susceptible to powdery mildew infection. Community composition also affected Knautia parents and offspring. In the presence of legumes, resident plants produced more seeds (increased fecundity); however, germination rate of those seeds was reduced at an early seedling stage (reduced fertility). Synthesis . We conclude that rapid transgenerational effects of community diversity and composition on both mean and variation of phenotypic traits among offspring exist. In addition to heritable variation, environmentally induced epigenetic and/or maternal processes matter for early plant community assembly and may also determine future species coexistence and community stability. Abstract : Plants occur in communities of few to many species. We observed diversity and composition of maternal communities to affect early, transgenerational phenotypic differentiation and variation of Knautia arvensis offspring under common garden conditions. We propose that environmentally induced epigenetic or maternal processes, in addition to heritable variation, matter for plant community assembly and may affect species coexistence and community stability. Photo: Powdery mildew infection ( Erysiphe knautiae, Duby) on K. arvensis residents in the Jena‐Experiment. Photo credit: Tanja Rottstock.